A Comparative Study of Arthroscopic Repair versus Open Surgical Techniques for the Management of Recurrent Anterior Shoulder Instability - C Ramesh Harish; Nara Srikanth (Asian Journal of Medical Research, 2019)
Background: To compare arthroscopic repair versus open surgical techniques for the management of recurrent anterior shoulder instability. Subjects and Methods: Fifty- eight patients with recurrent anterior shoulder instability of either gender were divided into 2 groups of 29 each. Group I comprised of patients managed with arthroscopic method and group II with open surgery. Modified Rowe score, ASES (American Shoulder and Elbow Society) score were recorded. Results: Group I had 15 males and 14 females and group II had 13 males and 16 females. The mean ROWE pain score at 4 weeks was 3.1 and 3.6 in group I and II respectively. The mean ROWE pain score at 4 weeks was 3.1 and 3.6 in group I and II respectively, at 6 weeks was 5.2 and 5.0 in group I and II respectively, at 9 weeks was 10.7 and 5.2 in group I and II respectively and at 12 weeks was 10.0 and 9.4 in group I and II respectively. The difference was non- significant (P> 0.05). The mean ASES pain score at 4 weeks was 2.9 and 1.4 in group I and II respectively, at 6 weeks was 4.6 and 2.3 in group I and II respectively, at 9 weeks was 2.9 and 2.1 in group I and II respectively and at 12 weeks was 3.7 and 3.2in group I and II respectively. The difference was non- significant (P> 0.05). Conclusion: Both techniques found to be equally effective in the management of cases of recurrent anterior shoulder instability.